Comparative Analysis of the Performance of Asphalt Concrete Mixtures with Modified Asphalt Using Rubber Latex - A Zikri; Makrifa, Auliya (Jurnal Handasah, 2025)
Industrial development in Indonesia is very rapid and has a positive impact on the economy of a region or country. The rubber industry, in particular, produces many benefits. However, the negative impacts that can arise from industrial products have the potential to pollute the environment, namely, waste in very large quantities and not utilized for activities that are beneficial to an area. Rubber Rubber Waste refers to leftover material or is the result of disposal from an industry which has little economic value and has a negative impact on the environment if it cannot be managed as well as possible.The Marshall method aims to determine the characteristics of a flexible pavement. This Marshall method consists of the Marshall Test and Marshall Parameters, namely Stability, Flow, MQ, VIM, VMA and VFA. Calibration factors for marshall equipment in the Al-Azhar Islamic University Mataram laboratory.The performance of Rubber Latex (Latex) as a mixture in AC-WC asphalt turns out to be quite influential because there is a decrease and increase in each mixture percentage on the VIM, VMA, VFA stability and flow values, when using a mixture of 5%, 6% 7%, there is a decrease in the value VIM, VFA, and stability were around 5-10%, and there was a 5% increase in the stability and flow values at mixture percentages of 5% and 9%. Rubber asphalt has a number of advantages over conventional concrete asphalt, especially in terms of flexibility, durability and comfort. However, the higher cost is a separate consideration when using it. The choice of type of asphalt to be used needs to be adjusted to traffic conditions, climate and available budget.